Hubungan Antara Pengetahuan Lingkungan Terhadap Sikap Peduli Lingkungan Mahasiswa Pendidikan Geografi Universitas Khairun - Rusman Rasyid; Andi Tenri Pada Agustang; Vrita Tri Aryuni; Tamrin Robo (Jurnal Ilmu Lingkungan, 2023)
This research is a correlation study that aims to determine the relationship between environmental knowledge and the formation of environmental care attitudes of students of Geography Education FKIP Khairun University. The population in this study amounted to 322 people with a sample of 76 people selected. Primary data collection in this study was through the provision of test questions related to environmental knowledge and environmental care attitudes, each of it had 30 question items. The data in this study were analyzed using the SPSS program by analyzing both descriptively through frequency distribution analysis and statistically through product moment correlation analysis. Based on the results of the descriptive analysis, it was found that most of the Geography Education students of Khairun University who became respondents had high environmental knowledge (75%), as well as their environmental care attitude was classified as good (96.05%). Meanwhile, based on the results of the product moment correlation analysis, a significance value of 0.000 was obtained, which was smaller than 0.05 (0.000 < 0.05), which means that there is a significant relationship between environmental knowledge and the formation of environmental care attitudes for Geography Education students at Khairun University.